2015
DOI: 10.1159/000375487
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation in the Effects of Induced Neonatal Hypoxia-Ischemia on Rapid Auditory Processing and Spatial Working Memory in Male Rats

Abstract: Infants born prematurely are at risk for cardiovascular events causing hypoxia-ischemia (HI; reduced blood and oxygen to the brain). HI in turn can cause neuropathology, though patterns of damage are sometimes diffuse and often highly variable (with clinical heterogeneity further magnified by rapid development). As a result, though HI injury is associated with long-term behavioral and cognitive impairments in general, pathology indices for specific infants can provide only limited insight into individual progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
(77 reference statements)
1
4
0
Order By: Relevance
“…Though the P7 HI rat was classically thought to model term infants with HIE, it is now thought to more accurately model insults seen in the late-preterm infant (GW 34–36; this new interpretation is reflected in updates to the website translatingtime.net, in which the Finlay group has calculated age comparisons between species (see [ 30 ])). Corresponding results confirm both neuropathologies and behavioral deficits typical of late-preterm HI insult in a P7 HI rat model [ 31 , 32 ]. Interestingly, in a recent study we have shown that mild temperature reduction during an HI insult led to “task-specific” benefits on a battery of behavioral tasks that generally favored females [ 33 ].…”
Section: Introductionsupporting
confidence: 70%
“…Though the P7 HI rat was classically thought to model term infants with HIE, it is now thought to more accurately model insults seen in the late-preterm infant (GW 34–36; this new interpretation is reflected in updates to the website translatingtime.net, in which the Finlay group has calculated age comparisons between species (see [ 30 ])). Corresponding results confirm both neuropathologies and behavioral deficits typical of late-preterm HI insult in a P7 HI rat model [ 31 , 32 ]. Interestingly, in a recent study we have shown that mild temperature reduction during an HI insult led to “task-specific” benefits on a battery of behavioral tasks that generally favored females [ 33 ].…”
Section: Introductionsupporting
confidence: 70%
“…Our lab and others have used the well-established Rice-Vannucci rat model of HI, where HI injury is experimentally induced on postnatal day (P) 7—roughly equating to injury in the late-preterm infant (34–36 gestational weeks (GW); [ 46 , 47 , 48 , 49 , 50 ]). Using this model, our lab has demonstrated behavioral deficits in male P7 HI rats, as assessed by tests of auditory processing, motor ability, spatial/non-spatial learning, working memory, and visual attention [ 25 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Our findings and those of others nicely parallel what is seen in the clinical population, thereby validating the use of the P7 HI model to study the consequences of neonatal HI.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors argue that P7 corresponds to 36 GW, which is still earlier than previously thought, with P10 being roughly equivalent to a term infant [ 89 ]. P7 HI male rats exhibit reliable deficits in rapid auditory processing as juveniles and adults, and deficits are persistent and stable within subjects [ 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. This follows other rodent models of language-related disabilities [ 106 , 107 , 108 , 109 , 110 , 111 , 112 ], and supports the idea that rapid acoustic processing deficits in animal models can serve as a biomarker of neural disruptions linked to language impairments [ 61 , 63 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Animal Models Of Preterm Brain Injurymentioning
confidence: 99%
“…Most pediatric associations agree that it should not be used in preterm infants, outside of a research setting, due to potential deleterious outcomes [ 20 ]. However, premature infants might benefit from an abbreviated and milder temperature reduction as shown below in work by Smith [ 103 , 104 ].…”
Section: Therapeutic Hypothermia For Neonatal Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation